Điều khiển được trong các hệ thống lớn - Châu, Nguyễn Văn (Journal of Computer Science and Cybernetics, 2016)
In this paper an approach is provide for presenting models of general systems in the sence of the theory of general systems and postulates. Basing on this model description some theorems on the controllability of generals systems will be proved. The theorems may allow us creating fast algorithms for checking the controllability of large scale and complicated systems.